Lactiplantibacillus sp. LP03 alleviates pulmonary fibrosis by modulating gut microbiota and elevating host palmitoylethanolamide to suppress TGF-β1/Smad2/3-mediated EMT - Zhou, Yuhao; Duan, Meina; Fan, Xiaoye; Zhao, Yuzhe; Wang, Chao; Wang, Tingting; Hua, Shucheng (Frontiers in Microbiology, 2025)
IntroductionIdiopathic pulmonary fibrosis (IPF) is a progressive and fatal interstitial lung disease with limited treatment options. Emerging evidence suggests that gut microbiota dysbiosis contributes to pulmonary disorders, underscoring the therapeutic potential of probiotics.MethodsThree Lactobacillus strains—Lactiplantibacillus sp. LP03 (LP03), Levilactobacillus brevis LB06, and Loigolactobacillus coryniformis LC0—were isolated from Chinese sauerkraut juice and evaluated in a bleomycin (BLM)-induced mouse model of pulmonary fibrosis. Gut microbiota composition was analyzed, and serum metabolomics profiling was performed to explore underlying mechanisms. Further, the therapeutic role of palmitoylethanolamide (PEA) was assessed both in vivo and in vitro.ResultsAmong the three strains, LP03 exhibited the most pronounced antifibrotic effects, including reduced mortality, systemic inflammation, lung coefficient, interstitial thickening, and collagen deposition, as well as inhibition of BLM-induced epithelial-to-mesenchymal transition (EMT). LP03 treatment restored gut microbial balance, notably increasing beneficial genera such as Ligilactobacillus and Akkermansia. Metabolomic analysis revealed enhanced lipid metabolism, especially in glycerophospholipid and fatty acid pathways, and elevated serum PEA levels. Oral PEA supplementation independently alleviated fibrosis, while mechanistic studies demonstrated that PEA mitigated fibrosis by inhibiting EMT through suppression of the TGF-β1/Smad2/3 signaling pathway.DiscussionThese findings highlight LP03 as a promising probiotic candidate for pulmonary fibrosis therapy. Its therapeutic effects are mediated by remodeling of the gut microbiota and elevation of systemic PEA, which in turn regulates fibrotic signaling pathways.